Preparative separation of the naphthopyranone glycosides by high-speed counter-current chromatography - dos Santos, L. C.; Vilegas, Wagner [UNESP] (Elsevier B.V., 2001)
High-speed counter-current chromatography was applied to the preparative separation and purification of naphthopyranone glycosides from a crude 70% ethanolic extract of the capitula of Paepalanthus microphyllus. The solvent system used was composed of water-ethanol-ethyl acetate-hexane (10:4:10:4, v/v). This technique led to the separation of four different naphthopyranone glycosides in pure form in only 7 h. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: counter-current chromatography; preparative chromatography; Paepalanthus microphyllus; glycosides; naphthopyranones; carbohydrates